Theoretical aspects of the management of building projects on the principles of "GREEN ECONOMICS" - Borokhovich, E. (Ways to Improve Construction Efficiency, 2019)
On the basis of theoretical analysis, the concept, principles, characteristics of the "green" economy, mentioned in various scientific publications, are generalized in the article. According to the results of the study, we propose to define the "green" economy as a model of economic development, based on sustainable development, a comprehensive approach to the process of making managerial decisions, improving the quality of life in the use of new technologies and innovations. In order to implement construction projects on the basis of the "green" economy, principles are proposed that take into account all aspects of sustainable development, as well as take into account the peculiarities of the institutional environment for the implementation of the construction project, the issue of integration and international cooperation.